Fibroblast Activation Protein Inhibitor Imaging in Nonmalignant Diseases: A New Perspective for Molecular Imaging - Schmidkonz, Christian; Kuwert, Torsten; Atzinger, Armin; Cordes, Michael; Schett, Georg; Ramming, Andreas; Götz, Theresa (Journal of Nuclear Medicine, 2022)
Fibroblast activation protein-α (FAP-α) is a type II transmembrane glycoprotein that is overexpressed in activated fibroblasts such as those in the stroma of tumors or in the fibrotic processes accompanying various benign diseases. The recent development and clinical implementation of radiolabeled quinolone-based tracers suitable for PET that act as FAP inhibitors (FAPIs) have opened a new perspective in molecular imaging. Although multiple studies have investigated the use of FAPI imaging in cancer, evidence concerning its use in nonmalignant diseases is still scarce. Herein, we provide a comprehensive review of FAPI imaging in nonmalignant diseases to clarify the current and potential role of this class of molecules in nuclear medicine.
CRIS-Team Scopus Importer:2022-12-16
Keywords: fibroblast activation protein; fibrosis; inflammatory diseases; molecular imaging; PET